Prevalence of ENT Diseases in Medical College for Women and Hospital, Dhaka - Six Months Retrospective Study (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Ear, Nose, Throat (ENT) & Head Neck diseases are very common in our country. Of course, patterns of ENT diseases vary depending on geographical distribution.Materials & methods: This retrospective study was carried out in ENT OPD in a tertiary hospital, Medical College for Women & Hospital (MCWH), Uttara, Dhaka, Bangladesh from July, 2015 to December, 2015. Total 3314 patients were selected for the study, males being 1582 & females, 1732. Cases were evaluated by local otolaryngologists by taking thorough history and clinical examination with proper and relevant investigations. Personal data included were age (1 month – 80 years) and sex. Information obtained was expressed in numbers and percentages with statistical analysis.Results: Top 10 diseases were selected which includes Chronic Suppurative Otitis Media (CSOM) 18.14%, Chronic tonsillitis 15.67%, Acute otitis media (AOM) 9.90%, Otitis externa (OE) 8.18%, Deviated nasal septum (DNS) 7.79%, Otitis media with effusion (OME) 7.27%, Allergic rhinitis (AR) 6.40%, Wax 4.98%, Pharyngitis 4.29%, Sinusitis 2.90%. The study reveals that the most vulnerable age group was 0-18 years. 47.74% and 52.26% were male and female respectively, the ratio being 0.9:1 that is almost equal. No significant differences were found in ENT diseases between males and females. Regarding infections of specific organs, CSOM was the most common and highest in order in our context followed by Ch. Tonsillitis, AOM, OE, DNS, OME, AR, Wax, Pharyngitis and Sinusitis.Conclusion:This study was made with an attempt to contribute to some extent to the epidemiologic profile of the common ENT & Head Neck diseases. It would probably enable the concerned personnel to enrich their knowledge and skill so that they can deal with the diseases properly.Bangladesh J Otorhinolaryngol 2022; 28(2): 186-192